Disentangling Pathways of Adolescent Sexual Risk from Problem Behavior Syndrome - Brookmeyer, Kathryn Amanda (2007)
Understanding the development of adolescent sexual risk behavior is complicated by the co-occurrence of sexual risk with substance use and delinquency, conceptualized as “problem behavior syndrome,” with common causes and influences underlying all three problem behaviors (Jessor & Jessor, 1977). Explaining the development of sexual risk becomes even more complex given the changing patterns of adaptation and maladaptation over the course of adolescence (Sroufe & Rutter, 1984). Research also suggests that multiple pathways may forecast adolescent engagement in sexual risk behavior, underscoring the ideas of equifinality and multifinality in developmental psychopathology (Cicchetti & Rogosh, 1996). To understand the diverse nature of sexual risk taking, researchers must identify these pathways and disentangle co-occurring problem behaviors from sexual risk. Revealing the course of sexual risk taking and the early risk and protective processes through which problem behavior develops allows researchers to identify the developmental periods that would be most amenable to intervention efforts (Rolf et al., 1990). Using data from the National Longitudinal Survey of Youth (NLSY79), this study aimed to disentangle problem behavior syndrome by identifying the unique developmental pathways of adolescent sexual risk, alcohol use and delinquency. This study also investigated how early adolescent processes of risk and protection were associated with the growth of these risk behaviors during adolescence. Using a developmental psychopathology and resilience framework, risk trajectories were measured with adolescents aged 15 to 24, and antecedents were measured with early adolescents ages 10 to 14 (N= 1778). Using Latent Class Growth Analyses (LCGA), joint trajectory analyses revealed five distinct adolescent risk taking groups: high sex and alcohol, moderate problem behavior, problem behavior, alcohol-only, and alcohol and delinquency experimentation. Early adolescent externalizing problems were particularly important in understanding adolescent risk group membership. The co-occurrence between sexual risk and alcohol use, the diversity of problem behavior syndrome, and potential intervention and prevention efforts are discussed